DAYA IMAJINASI DALAM AL-QUR’AN: ANALISIS STILISTIKA ATAS BAHASA AL-QUR’AN - Rahim, Abd. (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2024)
The function of imagination is related to the speaker's creative ability in building meaning and expression through language. Imaginary language style is a power of the Qur'an in affirming itself as the word of God. This language style is able to transform the dead symbols of the Qur'anic language into a series of meanings that are alive and moving in the minds of its readers. This study uses a qualitative methodology based on library research which goes through theoretical studies and analysis of the literature that will be the primary material for this writing. In this case, books that specifically discuss the language style of the Qur'an, books of interpretation and books related to the Qur'an in general. The results of this study are then described and used as an analytical tool for the verses of the Qur'an. Imaginary language style is widely used in expressing things that are still abstract, such as the beauty of heaven, the horror of hell and the chaos of the apocalypse. In the discipline of Arabic stylistics, this imagination can be expressed following the patterns of simile, metaphor, metonymy, and figures of speech. Each pattern has a distinctive background and impression